Indian Ocean Networks and the Transmutations of Servitude: The Protector of Indian Immigrants and the Administration of Freed Slaves and Indentured Labourers in Durban in the 1870s. Issue 3 (3rd May 2016) - Kaarsholm, Preben
Abstract : Focusing on Durban and its harbour, the article discusses the importation of different kinds of transnational bonded labour into Natal in the last half of the 19th century, and examines the ways in which Southern African and Indian Ocean histories were intertwined in the processes that built the colonial state. The institution of the Protector of Indian Immigrants is highlighted as a central ingredient in state building, which served to give legitimacy in regulating the supply of labour. The early history of the Protector's work in the 1870s is given special attention as regards the introduction into Natal of freed slaves from the Indian Ocean coast, of indentured labourers from India, and of 'Amatonga' migrant workers from Mozambique. An 1877 murder case is discussed, which led to the forced resignation of a Protector, as it threatened to undermine the respectability of the institution. The article shows the continuities that existed between forms of servitude from slavery and forced labour through the recruitment of 'liberated Africans' and indentured Indians to more recent types of migrant and voluntary wage labour.